2004
DOI: 10.21273/hortsci.39.5.987
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Seasonal Changes in Endogenous Plant Hormones and Alternate Bearing of Olive Trees

Abstract: Changes in hormone concentrations in leaf, node, shoot tip, and fruit samples of three Turkish olive (Olea europaea L.) cultivars (`Gemlik', `Memecik', and `Tavsan Yuregi') were monitored at monthly intervals over two successive years of the alternate-bearing cycle. Concentrations of abscisic acid (ABA), indole acetic acid (IAA), gibberellic acid-like substances (GA), and kinetin-like cytokinin were determined and their relationship to flower bud formation were examined durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 5 publications
1
23
1
Order By: Relevance
“…On the other hand, conflicting results for the relevance of the carbohydrate storage on reproductive development in olive trees have been reported. Thus, Ulger et al [7] indicated that the carbohydrates and mineral nutrients had trivial influence on the flower bud formation in the olive trees. Also, Bustan et al [38] suggested that the status of the carbohydrate reserves was not the main determinant for the alternate bearing, being rather involved in the survival of the olive trees.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, conflicting results for the relevance of the carbohydrate storage on reproductive development in olive trees have been reported. Thus, Ulger et al [7] indicated that the carbohydrates and mineral nutrients had trivial influence on the flower bud formation in the olive trees. Also, Bustan et al [38] suggested that the status of the carbohydrate reserves was not the main determinant for the alternate bearing, being rather involved in the survival of the olive trees.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, significant differences were revealed in the presence of some endogenous plant growth hormones including the abscisic acid (ABA), gibberellins like the gibberellic acids (GA 3 and GA 4 ) and auxins like the indole-3-acetic acid (IAA), between the “on” and “off” years for the olive tree samples [7], [54]. Thus, the floral formation was inhibited in the presence of high GA 3 levels, whereas the application of high concentrations of GA 4 , ABA and cytokinins resulted in elevated levels of flower formation in the olive tree [7]. It has been stated that high levels of GA 3 caused vegetative growth, negatively affecting the generative bud development in the following year.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, GAs were found to have a more direct and significant effect on the flower formation of many species than other PGRs. High GA levels showed an inhibitory effect on flower formation during induction and first periods (Dokoozlian and Peacock 2001;Baktir et al, 2004;Ulger et al, 2004;Achard and Genschik, 2009;Giacomelli et al, 2013;Kouret al, 2018). In contrast with gibberellins, abscisic acid (ABA) acts as a stress signal to regulate plant growth in response to changes in water availability.…”
Section: Introductionmentioning
confidence: 99%
“…The increase in ABA concentration has been associated with the onset of fruit ripening in non-climacteric fruits such as Citrus (Aung et al, 1991;Lafuente et al, 1997;Agustí et al, 2007), grape berries (Davies et al, 1997) and olive fruit (Baktir et al, 2004). Nevertheless, full development of colour occurs concomitantly with a decline in ABA concentration in Citrus but with an increase up to mid-ripening in grape berries, and with a continuous increase in olive.…”
Section: Discussionmentioning
confidence: 99%